Development of Interactive Chemistry Learning Devices using Domino Chemical Media in terms of Student Activity and Learning Outcomes of Class X High School in Samarinda - Medita Hermawanti; Mukhamad Nurhadi; Abdul Majid (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2018)
This research focuses on research and development of learning devices using Chemical Domino media. The product of this research is Interactive Chemical Domino learning media, which focused on compound nomenclature material for class X which is expected feasible to be used as learning media. The subjects in this study are divided into 2 stages, the first is the small group test in which only 12 students from SMA Negeri 1 Samarinda participate. The second is field test (large group) which 96 students from 3 high schools participate, namely SMA Negeri 1 Samarinda, 36 students from Madrasah Aliyah Negeri 2 Samarinda, and 36 students from SMA Negeri 5 Samarinda. The results showed that the validation of media experts scored 85.77%, material expert validation scored 88.63%. In learning media validation, it showed that validation of RPP scored 92.08%, LKS validation scored 92.67%. For student response results scored 81.25%. From those scores it can be concluded that development of learning device using Media Chemical Domino is "very good”. Meanwhile for the observation results of student activity increased up to 33.71% and for student learning results from posttest and daily test reach KKM with percentage of student learning result 77,34%.